Caracterización de espacios de Banach mediante desigualdades y el mapeo de dualidad - Ugalde, William J. (2007)
Using a result of C. E. Chidume, we present a shorter and improved proof of a result of Xu and Roach on characterization of uniformly convex and uniformly smooth Banach spaces by the duality map and inequalities involving strictly increasing and strictly decreasing functions.